Objective Assessment of Ocular Surface Response to Contact Lens Wear in Presbyopic Contact Lens Wearers of Asian Descent. Issue 3 (May 2018) - Guillon, Michel; Dumbleton, Kathy; Theodoratos, Panagiotis; Patel, Trisha; Karkkainen, Tom; Moody, Kurt
Abstract : Introduction: Contact lens wearers of Asian descent may be predisposed to experience microtrauma of the ocular surface as a result a thinner post-lens tear film and higher eyelid tension, and these effects would be anticipated to be most marked in an older population. The objective of this study was to quantify the mechanical effects of the study contact lenses on the ocular surface in a population of presbyopic contact lens wearers of Asian descent. Methods: Twenty established presbyopic contact lens wearers (hydrogel n=5, none habitual wearers of etafilcon A lenses; silicone hydrogel n=15) of Asian descent were refitted with etafilcon A multifocal daily disposable contact lenses (1-DAY ACUVUE MOIST MULTIFOCAL) for a period of 1 month of daily lens wear. The habitual modalities of wear were 45% daily disposable and 55% planned replacement. Digital photographs of the upper lid margins, nasal and temporal conjunctiva, and superior cornea were taken after 6 hr of wear of the participants' habitual contact lenses, after 1 day without contact lens wear, and after 6 hr of wear of the study contact lenses at the end of the 1-month period. The photographs were masked according to study visit and the staining extent measured using proprietary software. Results: Lid margin staining was significantly lower with the study contact lenses (2.0±1.0 mm 2 ) than with the participants' own contact lenses (3.2±3.0 mm 2 ) after 6 hr of wear, representing a mean staining decrease of 38% ( P =0.010). Lid margin staining after 6 hr of wear of the study contact lenses was not different from that measured after 1 day without contact lenses ( P =0.507). Limbal staining was also significantly less with the study contact lenses than with the participants' own contact lenses after 6 hr of wear ( P =0.009). There was minimal upper corneal staining, and the degree was similar with the study and habitual lenses. Conclusions: Etafilcon A material, worn under a daily disposable modality, was shown to reduce upper lid margin and limbal staining in presbyopic contact lens wearers of Asian descent compared with the wearers' own contact lenses. Because of the high preponderance of dry eye amongst presbyopes, material selection is of importance and consideration should be given to the lens–ocular surface interaction.